PEMBERIAN HARTA WARIS TERHADAP ANAK DIBAWAH UMUR DALAM PERSPEKTIF HUKUM ISLAM - Umami, Hafidhul; Novianta Ahsana (ADIDAS: Asosiasi Dosen Syari'ah STAI Darussalam Nganjuk, 2025)
The inheritance of minors remains a crucial topic in Islamic inheritance law, reflecting the religion’s commitment to justice and protection of vulnerable heirs. Islamic law, as detailed in the Qur’an and Hadith, not only specifies the shares of each heir but also emphasizes the safeguarding of minors who are legally incapable of managing their inherited assets. These protections include the appointment of a responsible guardian (wali) to manage the estate on behalf of the child until they reach legal maturity or are deemed capable by law. The guardian is entrusted to act with integrity, avoiding misappropriation, and to ensure that the child’s property is preserved and utilized in their best interest. This paper discusses the legal foundations, procedures, and ethical responsibilities surrounding the inheritance rights of minors in Islam. It also highlights the broader implications of this legal framework in ensuring social justice and the preservation of wealth within the family unit.